Peran Pembangunan untuk Mengukuhkan Nasionalisme dan Membangun Karakter Bangsa - Edy Suandi Hamid (Unisia, 2012)
Nationalism as an ideological concept is considered to be one among important aspects in the creation of the character of the nation, including Indonesians, The character building for the nation in turn will determine the quality of the nation. The process of development within countries across the globe is partly shaped its success by the characters of the respective nation. The inception of such ideological concept can be efficiently introduced through many channels, and education is a channel that can be utilized optimally to internalize the nationalism to the students' personality. It is considered therefore that certain ways of education that may support the internalization of such ideology need to be enhanced.Key words: nationalism, education, character